Peran Brand Awareness dalam Memediasi Pengaruh Digital Advertising dan Flash Sale terhadap Keputusan Pembelian di TikTok Shop - Giovvani Angela Gunawan; Kadek Devi Kalfika Anggria Wardani; Made Mulyadi; Kadek Wulandari Laksmi P. (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the role of brand awareness in mediating the effect of digital advertising and flash sale promotions on purchase decisions on TikTok Shop. Along with the shift in shopping behavior toward digital platforms, social commerce platforms such as TikTok Shop have become highly competitive arenas that require a comprehensive understanding of the factors driving consumer transactions. This research adopts a quantitative approach, with data collected through questionnaires distributed to 190 TikTok Shop users in Denpasar City. The sampling technique employed was proportional stratified random sampling across four districts in Denpasar City. The collected data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach through SmartPLS 4.0 software. The results indicate that digital advertising and flash sale promotions have a positive and significant effect on purchase decisions. In addition, both variables also have a positive and significant effect on TikTok Shop platform brand awareness. TikTok Shop brand awareness is proven to have a positive and significant effect on purchase decisions and serves as a partial mediating variable in the relationship between digital advertising and flash sale promotions and users’ purchase decisions on TikTok Shop.